High mobility ReSe2 field effect transistors: Schottky-barrier-height-dependent photoresponsivity and broadband light detection with Co decoration. (4th November 2019) - Khan, Muhammad Farooq; Rehman, Shania; Akhtar, Imtisal; Aftab, Sikandar; Ajmal, Hafiz Muhammad Salman; Khan, Waqar; Kim, Deok-kee; Eom, Jonghwa
Abstract: 2D transition metal dichalcogenides are promising in various electronics and optoelectronics applications and have gained popularity owing to their carrier transport and strong light–matter interactions. To fully realize their potential in field-effect transistors (FETs) and photodetectors, high mobility and high responsivity are imperative. Here, we demonstrate the highest mobility of 166 cm 2 V −1 s −1 at 200 K for single-layer rhenium diselenide (ReSe2 ) FETs encapsulated between h-BN flakes at V g = 47 V. The high mobility is attributed to low-resistance contacts of scandium/gold (Sc/Au), with a low Schottky barrier height and reduced charge scattering platform of h-BN. Further, we elucidated the Schottky-barrier-height dependent high photoresponsivity ( 3.2 × 10 6 A W −1 ) of few-layer ReSe2 (FL-ReSe2 ) at 532 nm-wavelength laser light on an h-BN substrate with Sc/Au contacts. Moreover, broadband light detection of undoped and Co-doped few-layer (FL) ReSe2 was performed under different laser wavelengths (400–1100 nm). After the deposition of Co nanoparticles, the photocurrent of FL-ReSe2 increased due to n-doping, as confirmed by the transfer curves of the FL-ReSe2 -based undoped and co-doped FETs. Further, the work function decreased from 4.856 to 4.791 eV in FL-ReSe2, as measured by Kelvin probe force microscopy. No light signal was observed at 1100 nm for the undoped ReSe2 (1050 nm < λ cut-off < 1100 nm); however, after doping with Co nanoparticles, the cut-off wavelength exceeded to ( λ cut-off > 1100 nm), due to the additional trap states generated in the energy band gap of ReSe2 after Co doping. Further, the transient response of ReSe2 and Co + ReSe2 FETs was estimated so that the rise and decay times are decreased from 1.9 s & 2.7 s to 1.1 s & 1.8 s, respectively. ReSe2 is therefore a promising semiconducting material for electrical and optoelectrical applications.